Understanding Non-compliance With Protected Species Regulations in the Northeast USA Gillnet Fishery - Bisack, Kathryn D.; Das, Chhandita (Frontiers in Marine Science, 2015)
Marine mammals and sea turtles in the United States are protected from commercial fishery interactions under the Marine Mammal Protection Act and the Endangered Species Act. To reduce harbor porpoise bycatch in the northeast sink gillnet fishery, fishermen are mandated to attach pingers to their nets in regulated areas. Although, pinger regulations have been in place for over a decade, in practice, enforcement is weak and the penalty for a violation is almost non-existent. In this scenario, the presence of normative factors may motivate a fisherman to comply with the pinger regulation. This study considers both economic and normative factors within a probit framework to explain a fisherman’s compliance decision. Model results indicate fishermen who previously violated pinger regulations, who are not completely dependent on gillnet gear and face a lower chance of being detected by an observer, are more likely to violate. Understanding the influence of normative factors on compliance decisions is a key component for higher compliance. That is, incorporation of these factors in the design of policy instruments may achieve higher compliance rates and thus more success in protecting these species. Our model findings were ground-truthed by conducting focus group research with fishermen using pingers; some preliminary findings are shared in the discussion in support of our model results. Finally, these results also suggest observer data can be used to support compliance and enforcement mechanisms in this fishery and possibly other fisheries as well.